VECTOR FIELDS TANGENT TO FOLIATIONS - Martins, L. F. [UNESP]; Tari, F. (Cambridge University Press, 2008)
We investigate in this paper the topological stability of pairs (omega, X), where w is a germ of an integrable 1-form and X is a germ of a vector field tangent to the foliation determined by omega.
Keywords: 1-form; foliation; singularity; topological stability; vector field